Extremalindikator der ganzen Funktionen mit positiven Nullstellen. II - Kondratjuk, A. (Lithuanian Mathematical Journal, 1968)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:А. А. Кондратюк. Экстремальный индикатор для целых функций с положительными нулями. IIA. Kondratjuk. Sveikų funkcijų su teigiamais nuliais ekstremalinis indikatorius. II